The Role of Megalobrama amblycephala bcl2l13 Gene in Apoptosis and Autophagy - Suzhen Wang; Xuanhui Li; Danyang Wu; Zexia Gao; Hong Liu; Huanling Wang (Fishes)
Bcl-2-like protein 13 (Bcl2l13) plays an important role in the cell apoptosis and mitochondrial autophagy of mammals. However, the role of bcl2l13 remains unclear in fish. Therefore, in this study, the function of Megalobrama amblycephala bcl2l13 gene in apoptosis and autophagy was investigated. The results showed that the overexpression of M. amblycephala bcl2l13 under hypoxic condition led to a reduction of reactive oxygen species (ROS), an increase in the expression levels of autophagy-related genes (p62, lc3, pink1), and a disruption of mitochondrial structure. However, deleting its transmembrane (TM) and Bcl-2 homology no (BHNo) domains decreased the P62 protein level, suggesting its essential role in autophagy. Furthermore, bcl2l13 overexpression inhibited cell proliferation and increased apoptosis. Additional studies revealed that the permeability of the mitochondrial permeability transition pore (mPTP) increased after overexpression of bcl2l13, but decreased upon deletion of the TM domain. Additionally, hypoxia led to elevated Bcl2l13 and P62 levels, and caused mitochondrial damage in M. amblycephala liver after 48 h of treatment. In conclusion, bcl2l13 may induce autophagy, inhibit cell proliferation and promote apoptosis, while its TM and BHNo domains play pivotal roles in these processes.